Awakening local tourism based on indische architecture in Indonesia. Case study Kajoetangan Kampong heritage of Malang - Pramono, Wahyu Tyas; Anggriani, Swastika Dhesti; Meiji, Nanda Harda Pratama; Ujang, Norsidah; Sayono, Joko (Editura Universitati din Oradea, 2021)
Kajoetangan or Kayutangan kampong heritage is a new tourist spot in Malang that emphasizes the empowerment of local communities in realizing settlement-based sustainable tourism that existed during the colonial era which was composed of dozens of Indische architecture in the late 19th to early 20th centuries. Kayutangan heritage villages are composed of settlements with a small size with access in the form of a small footpath combined with a mural and various outdoor plants. The houses in the area have not changed for nearly a hundred years, which have been passed down from generation to generation. Descriptive qualitative method is used in this research by combining the data obtained based on in-depth interviews, survey and combined with literature studies. Purpose of this research is to explore historical sequences and processes of sustainable tourism management controlled by local residents with financial assistance from various partners. The results of the study show that the role of local communities is quite positive in efforts to support tourists either by being directly or indirectly involved by building supporting facilities for core tourism such as culinary spots and souvenirs. Collaboration with several government agencies, universities and banks also makes the additions and directions in making and using additional facilities more structured.